Risks of infection associated with aerosol generation during medical procedures in an endoscopy unit - Pereira M.L. (2022)
© 2022Several medical procedures for treatment or diagnosis of diseases have been identified as potentially aerosol generators. The aim of this study is to investigate the potential exposure of the health professionals to aerosols generation during different medical procedures in a hospital endoscopy unit, and to characterize the emitted aerosols in terms of airborne concentration and size. Aerosols number concentrations and sizes, were measured and indoor activity was collected and correlated with the emitting sources. Endoscopy, bronchoscopy, colonoscopy, and bidirectional endoscopy procedures were identified as the most important aerosol sources. During these procedures, the increases in mean aerosols concentration (< 5 µm) in relation to the reference concentration for colonoscopy, upper endoscopy, bronchoscopy and bidirectional endoscopy procedures were 12, 72, 39, and 141%, respectively. These results showed that, depending on the type of activity performed inside the room, the concentration of aerosols varied considerably in relation to the reference concentration. The results also demonstrated that aerosols generation events during medical procedures in an endoscopy unit are divided into two categories: the events that create and disperse aerosols mechanically and events that induce the patient to produce aerosols.In the SARS-CoV-2 context, the virus stability characteristics and modes of transmission make all sources analyzed as high risk for COVID-19 transmission.